Mabādi’ al-Tahżīb fī al-Naṣ al-Masrohy “al-Dūdah wa al Ṡu’bān” li ‘aly Ahmad ba Kaṡīr ‘alā Asāsi nadzariyyah Geoffrey Leech - Isna Nur Azizah (Journal of Arabic Literature (JaLi), 2022)
Abstract: Politeness is an important principle in communication. Because in communicating it is necessary to consider the feelings of others by maximizing benefits for others and minimizing losses for others so that good communication will be created without embarrass the interlocutor. This study aims to: (1) determine the form of compliance with the principles of politeness in the drama script Ad-Duddah Wa Tsu'ban by Ali Ahmad Bakatsir based on the perspective of Geoffrey Leech; and (2) knowing the form of violation of politeness principles in the drama script Ad-Duddah Wa Tsu'ban by Ali Ahmad Bakatsir based on the perspective of Geoffrey Leech. his study uses a descriptive qualitative research, with primary data sources being the drama script Ad-Duddah Wa Tsu'ban by Ali Ahmad Bakatsir and secondary data sources in the form of books and articles in scientific journals that explain the principles of politeness based on the perspective of Geoffrey Leech. The research technique used in this research is reading technique and note-taking technique. The data analysis technique used is data reduction, display data and conclusion drawing. The results of this study are (1) found form of fulfillment of politeness principles as many as 31 utterances which include 8 utterances of the maxims of wisdom, 4 utterances of the maxims of generosity, 6 utterances of the maxims of appreciation, 3 utterances of the maxims of humility, 6 utterances of the maxims of consensus, and 4 utterances of the maxims of sympathy; and (2) there are 21 forms of violation of politeness principle which include 7 utterance of the maxim of wisdom, 3 utterances of the maxim of appreciation, 2 utterance of the maxim of generosity, 1 utterance of the maxim of humility, 7 utterance of the maxim of consensus, and 1 utterances of the maxim of sympathy. All these utterances are considered to fulfill and violate the principle of politeness according to Geoffrey Leech by looking at the elements and concepts that already exis.